Fight or flight? overcoming panic and agoraphobia - Rapee, Ronald M.; Guilford Publications, Inc.; Monkey See Productions (New York : Guilford Publications, 1998)
Portrays the experience of panic disorder with agoraphobia and shows how cognitive-behavioral therapy can provide the skills that sufferers need to attain relief. Detailed accounts from actual clients are accompanied by a step-by-step overview of treatment from cognitive-behavioral therapy specialists. Components described include self-monitoring, controlled breathing, realistic thinking, and internal and external exposure. Also covered are the physical symptoms of anxiety, the risks and benefits of medications, the role of group treatment, and how to maintain gains over time
Keywords: Panic Disorder -- therapy; Agoraphobia -- therapy; Cognitive Therapy -- methods